Public health education at China's higher education institutions: a time-series analysis from 1998 to 2012 - Jianlin Hou; Zhifeng Wang; Xiaoyun Liu; Youhui Luo; Sabhyta Sabharwal; Nan Wang; Qingyue Meng (BMC, 2018)
Abstract Background Although China's modern education for public health was developing over the past 60 years, there is a lack of authoritative statistics and analyses on the nation's development of education for public health at higher education institutions (HEIs). Few quantitative studies on this topic have been published in domestic and international peer-reviewed journals. To address this knowledge gap, we aimed to use national data to quantitatively analyse the scale, structure, and changes of public health education in China's HEIs, and to compare the changes of public health education with those of other health science disciplines. Methods This study uses previously unreleased national data provided by the Ministry of Education of China that includes the number of health professional students by school and major. The data, which spans from 1998 to 2012, are descriptively analyzed. Results The number of HEIs for public health education per 100 million population increased from 7.2 in 1998 to 11.3 in 2012. The total enrolment, number of students, and number of graduates increased at rates of 7.3, 7.4, and 5.8% per year, respectively. The percentage of junior college students dropped drastically from 24.0 to 8.4% from 1998 to 2012. During that same period, the number of undergraduates, master and doctorate students increased. Undergraduates accounted for the majority of public health graduates (63.1%) in 2012, and master and doctorate students increased by 10.0 and 5.1 times, respectively, from 1998 to 2012. The relative percentage of public health enrollment, students, and graduates to all health education disciplines dropped from about 6.0% percent in 1998 to around 2% in 2012. Conclusions The overall scale of public health education has clearly expanded, though at a slower pace than many other health science disciplines in China. The increase of public health graduates helped to address the previous shortage of public health professionals. Gradually adopting a modern model of education, public health education in China has undergone notable changes that may be informative to other developing countries though it still faces a complex situation in terms of graduates' adherence to public health, student recruitment, teaching and training, program planning and reform.